Antibacterial efficacy of prophylactic ozone treatment on patients with fixed orthodontic appliances. (1st November 2013) - Aykut-Yetkiner, Arzu; Eden, Ece; Ertuğrul, Fahinur; Ergin, Ecem; AteŞ, Mustafa
Abstract: Objective. This study investigated the efficacy of ozone on microflora of patients with fixed orthodontic appliances. Materials and methods. Ten subjects undergoing fixed appliance therapy were enrolled in the study. Before any application, two elastic ligatures were removed with the aid of a sterile probe from the premolar brackets on the upper right and lower left jaws for baseline bacteriological counts. Then ozone gas was applied for 180 s by running the device on prophylaxis mode with included mouth tray according to the manufacturer's recommendations on all brackets. After the ozone application, two other elastic ligatures were removed from the opposite sides of the mouth of the patients. One week after the application two more elastic samples, which were not changed in the previous session, were collected from the upper right and lower left premolar brackets. The elastic ligatures were immersed in transfer solutions and cultured to determine the Streptococcus mutans and Lactobacillus acidophilus. Statistical analysis of the data was obtained by paired Student's t -tests. Results. The ozone treatment reduced the S. mutans and L. acidophilus immediately after the application and these reductions were found to be statistically significant ( p = 0.038 and p = 0.020). Both the S. mutans and L. acidophilus values increased by the 1-week period and the S. mutans values were significantly higher than the baseline values ( p = 0.01). Conclusion. It can be concluded that the ozone treatment may have an instantaneous lethal effect on S. mutans and L. acidophilus; however, within the limitations of this study, a long-term preventive effect could not be observed.